English Teaching at SMAN 1 Bungo in Before, During, and After the Covid-19 Pandemic - Viona Chairina; Ainul Addinna (Journal of English Language Teaching, 2022)
This study was conducted to determine about English teaching at SMAN 1 Bungo before, during, and after the covid 19 pandemic. This study used qualitative descriptive as its methodology. The population for this study were 3 teachers which had experience in teaching before, during, and after the Covid 19 pandemic at SMAN 1 Bungo. The researcher used a voice recorder to record the process of the Interview. Following data collection, there are six variables that became the focus in the research. The variable came from 4 books that have been released by Brown in Second Edition (2001) and Fifith Edition (2007), Scrivener (2010) in Third Edition, and Harmer (2001) in Third Edition. For the conclusion, Teachers 1, 2, and 3 in carrying out English language teaching were considered good because it used almost all of the variable that the experts suggested during before the pandemic. Meanwhile in the pandemic, the numerous limitations that students and teachers faced such as interaction between teacher and student only on WhatsApp and Portal Belajar Dari Rumah (BDR) and no direct learning. So, the implementation was not implemented much. And after the COVID-19 pandemic, teachers 1, 2, and 3 returned all the interact with students the same as before the pandemic.